Hypnosis as an Alternative to General Anesthesia for Orthopedic Hand Surgery: A Case Report - Fathi, Mehdi; Hassani, Mohammad; Jafari, Mahdieh; Joudi, Marjan; Habibzadeh, Reza; Joudi, Mitra (Annals of Anesthesiology and Critical Care, 2017)
The effectiveness of psychological techniques such as patient education, cognitive and behavioral interventions, relaxation techniques, hypnosis, therapeutic suggestion interventions, and emotion-focused interventions has been assessed through the outcomes of postoperative pain, perioperative anxiety, quality of life, and recovery in adults. In this case presentation, we introduce using of hypnosis as an approach to pain control in hand surgery.